Maceration affects mineral composition and pH of wines - Rakonczás, N.; Andrási, D.; Murányi, Z. (International Journal of Horticultural Science, 2015)
Mineral composition of wines is affected by many ecological and technological factors. These variables are mostly discussed focusing on certification of origin and human health. This paper gives data on possible changes in mineral composition and pH of wines due to 4 hours skin maceration (1st trial) and fermentation sur marc (2nd trial). Experimental site is situated on acidic sandy soil in middle east Hungary. The variety collection was established in 2003 with own rooted planting material in 3x1 m spacing, trained for single curtain training system. Mineral composition of wines was determined with ThermoFischer Scientific iCAP 6300 ICP-OES, pH was measured with pH10pen (VWR International) in field, and with SevenEasyTM pH meter (Mettler Toledo) in laboratory. 1st trial with 9 PIWI white wine grape varieties pointed to demonstrate effects of skin maceration, which is abundantly used to elevate aroma content. 2nd trial with the use of ‘Medina’ red PIWI grape variety aimed to demonstrate effects of double pasta skin maceration in rose and red wine technology. Data of 1st trial show, that K, Cu, Mn and P respective increase with skin maceration, despite Fe show considerable decrease. Data of 2nd trial show, that K, Mg, Mn, P, Sr and B increase with longer skin contact and higher fermentation temperature, despite Fe and Ba decrease with this technology. In regard to pH, data show, that skin maceration and fermentation sur marc increase K content with about 30-70% respectively, withstanding that pH also increase with a considerable 0,4-0,5 value. K content can be higher in the end product, despite to earlier higher level of tartrate formation. An attention should be driven to lower level of tartaric acid and consequently higher pH characteristic for wines produced with the application of skin maceration or fermentation sur marc.